The Concretization of the Precautionary Principle under the Regulation of the Minister of Environment and Forestry Number 14 of 2023 in Resolving Existing Businesses and/or Activities within the Rawa Singkil Wildlife Reserve. - Kartika, Iin Kartika; Yanis Rinaldi; Muazzin Muazzin (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This research is motivated by the enactment of the Regulation of the Minister of Environment and Forestry Number 14 of 2023, which regulates the settlement of existing businesses and/or activities within conservation areas, including the Rawa Singkil Wildlife Reserve in Aceh, an area with significant ecological functions as a wildlife habitat and a strategic peatland ecosystem. The implementation of the conservation partnership scheme under this regulation raises legal issues concerning the balance between resolving existing activities and maintaining the ecological functions of conservation areas. This study aims to analyze the concretization of the precautionary principle in the Regulation of the Minister of Environment and Forestry Number 14 of 2023 and its juridical implications for the protection of the Rawa Singkil Wildlife Reserve.This research employs normative legal research using statutory and conceptual approaches. Primary, secondary, and tertiary legal materials are analyzed qualitatively based on the precautionary principle, the theory of the hierarchy of norms, legal harmonization theory, and legal protection theory. The results indicate that the concretization of the precautionary principle in the regulation remains partial and predominantly administrative in nature. Although it has been implemented through inventory, verification, activity restrictions, ecosystem restoration, and monitoring and evaluation mechanisms, the regulation has not yet positioned ecological risks, area sensitivity, and the potential for irreversible environmental damage as the primary parameters in determining settlement measures. The implementation of the Regulation of the Minister of Environment and Forestry Number 14 of 2023 in the Rawa Singkil Wildlife Reserve may provide legal certainty and strengthen conservation protection if it is directed toward ecosystem restoration, effective supervision, and the return of areas to the state. However, the application of the conservation partnership scheme without rigorous ecological risk analysis has the potential to weaken the protection of peatland hydrological functions and wildlife habitats. Therefore, this regulation should be revised by placing the protection of ecological functions of conservation areas and ecological risk assessment as the main parameters in resolving existing businesses and/or activities.